Lithology Combination Identification Method Based on Discrete Wavelet Transform and Its Application - JIAO Guohua (Cejing jishu)
In the process of ultra-deep oil and gas exploration, it is difficult to identify reservoir lithology combination due to the high cost and small number of real drilling and the strong multi-solution of logging curves, which further affects the accuracy of sedimentary facies and reservoir sweet spot prediction. Based on the wavelet transform of natural gamma curve, the logging signals are decomposed by discrete wavelet, and the characteristics of lithologic combinations corresponding to different energy groups on the time-frequency energy diagram are summarized. Taking the ultra-deep tight sandstone reservoir of Zheng1 well in Zhengshacun area of Junggar basin as an example, through the discrete wavelet transform analysis of natural gamma curve with sensitive parameters of mud content, the identification of different lithologic combinations with appropriate scales is made. This method has the value of popularization in the same type of reservoir.